A tie between educational institution and industry: a case study of benefit from work-based learning - Ismail, Syamhanim; Mohamad, Mimi Mohaffyza; Mohd Faiz, Nur Sofurah (Penerbit UTHM, 2021)
Work-Based Learning (WBL) is the learning methodology that uses two workplaces: educational institutions and industries. WBL connects the knowledge and approaches in workplaces by reciprocal sharing of the theory from educational institutions and expertise in technical skills by industries. This research explores the experience of connecting the knowledge and approaches in workplaces between institutions and the industry via three pilot programs that apply WBL methods: The Networking Advanced Diploma, Bachelor of Facility Management with Honors and Bachelor of Computer Engineering Technology (Medical) with Honors. This study employed a multiple case study of qualitative approach. The data collections in the field study were conducted using in-depth, face-to-face interviews and semi-structured protocol with the three participants from polytechnics and five participants from the industry. The findings showed that WBL could connect the knowledge and approaches in workplaces by sharing the educational information, technical skill and technology between institution and industry. The findings also show that industrial attachment and win-win situations happen in WBL. Based on the results of this study, hopefully, there are more ways to connect knowledge and approaches between institutions and the industry to ensure the sustainability of WBL programs.